NGOs CONTESTATION ON ISLAMIC HIJRI CALENDAR IN URBAN MUSLIM SOCIETY IN INDONESIA: FROM AUTHORITY TO IDENTITY - Rofiuddin, Ahmad Adib; Hakim, Ahmad Luqman (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Institut Agama Islam Negeri Metro, 2022)
This article discusses on religious contestation on determination of Islamic Calendar in Urban Muslim society in Indonesia. An Indonesian Islamic calendar discourse is always dominated by Nahdatul Ulama and Muhammadiyah as two largest Islamic NGOs. The choice of individuals from this group to fill the office of Minister of Religious Affairs, the official authority, is a sign of the domination amongst these mass organizations. To analyze the contestation of religious authority, this paper recommends the application of an analytical framework of the Gramsci’s hegemony theory which illustrates the contestation between them. Data were gathered through in-depth interviews with the two organizations' experts in Islamic astronomy, which were then evaluated using a descriptive approach. The finding of this paper reveal that the contestation between Nahdatul Ulama and Muhammadiyah not only in relation to the power, but also strengthening the identity of each group to shows their power on Islamic Calendar discourse in Indonesia.